Polycrystalline Ho:YAG transparent ceramics for eye-safe solid state laser applications - Yang, Hao (2013)
High optical quality holmium doped yttrium aluminum garnet (Ho:YAG) transparent ceramics that contained 0.5–2.0 at.% holmium additives were fabricated by a reactive sintering method under vacuum. Fully dense Ho:YAG ceramics with the average grain size of ~10 μm were obtained after vacuum sintered at 1780°C for 8 h. The in-line transmittances in the visible and infrared region are higher than 82% and 84%. The absorption coefficients of the 0.8, 1.0, 1.5, and 2.0 at.% Ho:YAG ceramics at 1907 nm was calculated to be 0.72, 0.89, 1.32, and 1.78 cm−1, respectively. The absorption cross-section of Ho:YAG ceramic was 0.645 × 10−20 cm2. The 1.5 and 2.0 at.% Ho:YAG ceramic slabs were in-band pumped by a Tm:fiber laser at 1907 nm. A maximum output power of 20.6 W at 2097 nm was obtained with a corresponding slope efficiency of 60.9%.